Awareness of purchasing skin care products: a case study among students in UiTM Kota Bharu / Hafizah Harun, Norerney Sazfizza Saifuzzaman and Nurul Arina Nabilah Zaharudin - Harun, Hafizah; Saifuzzaman, Norerney Sazfizza; Zaharudin, Nurul Arina Nabilah (2019)
Nowadays, everyone wants to look flawless and has youthful face, but it is not impossible for them to achieve it. According to Krupp (2008), ladies spend about $470 million a year on skin care products and they often purchase several products since they are using different products for their morning and night routines. This study was canied out to identify the factors that influence the awareness of purchasing skin care products among students in UiTM Kota Bharu. The objective in this study is to measure the relationship between the factors (internal influence, economic and marketing) and the awareness of purchasing skin care products among UiTM Kota Bharu students. The second objective is to determine the factors (internal influence, economic and marketing) that influence the awareness of purchasing skin care products among UiTM Kota Bharu students. The third objective is to study the mean difference in awareness of purchasing skin care product between two sources of income (PTPTN and family income) among students in UiTM Kota Bharu. The study used simple random sampling to select a sample of 221 respondents from UiTM Kota Bharu students. The study was conducted using self-administration questionnaire through Google form for different students' courses and semesters. This study decided to use multiple linear regression. In conclusion, the findings showed that there was a significant relationship between all variables and moderate positive linear relationship between internal influence (X1), economic factor (X2) and marketing factor (X3) towards awareness of purchasing skin care (Y). Next, the result showed that only two variables were significant to the model which included internal influence and marketing factor. Lastly, based on the findings, it can be concluded that there was no significant difference in awareness of purchasing skin care product between sources of income (PTPTN and family income) among students in UiTM Kota Bharu. It is recommended that future study increase the sample size to produce more effective results and findings.